Calculation of Environmental Services For The Forest Adoption Plot of PT Bio Farma (Persero) In Taman Buru Masigit Kareumbi, West Java - Yusuf Nugraha Andrian; Ratna Wingit; Nida Aulia Ulhaq (Return : Study of Management, Economic and Bussines, 2023)
Climate change or global warming has always been a hot topic of discussion and a global issue. Forests, as one of the largest carbon sinks, play a crucial role in addressing the problem of global warming. Forests have direct benefits that can be felt by humans, as well as indirect benefits that are not directly experienced by humans. One of the indirect benefits felt by humans is the absorption of CO2 and the production of O2. Taman Buru Masigit Kareumbi (TBMK) is a conservation area that plays an important role in the absorption of CO2 and the production of O2. Taman Buru Masigit Kareumbi does not have a buffer zone, which creates significant pressure on the area, especially social pressure. The significant pressure on the area has led to the emergence of the Forest Adoption program there. This program is aimed at the care and protection of forest areas through an adoption scheme. PT Bio Farma (Persero) actively participates in this program. The Forest Adoption plot of PT Bio Farma (Persero) has a carbon reserve of 134,095 tons, a CO2 absorption value of 418,464 tons/hectare/year, and an O2 production value of 358,033 tons/hectare/year. When evaluated, the Forest Adoption plot of PT Bio Farma (Persero) has a carbon absorption value of Rp. 28,318,422 (twenty-eight million three hundred eighteen thousand four hundred twenty-two Indonesian rupiah).